Determinants De L’efficacite Technique Des Exploitations Avicoles Familiales A Kinshasa En Rd. Congo - Nkusu Wati, Espérant; Muayila Kabibu, Henry; Binm Mukanya, Moïse Kalambaie; Muyombo Mutatshi, Richard; Muyene Miyuku, Faustin (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aims to identify the explanatory factors of the technical efficiency of family poultry farms in Kinshasa, to evaluating their levels of efficiency, to determine the yield zone operated by the farms.The data envelopment analysis model was used and determine the area of scale yields in which 44 wine producers from 3 communes including Mont-ngafula, Nsele and Maluku operate in the province of Kinshasa drawn using the technique non-probability participation ; and finally the tobit regression to identify the main covariates of technical efficiency.The result  revealed that average level of technical efficiency scores is 0,455 under the assumption of constant returns to scale ; 0,498, when returns to are assumed to be variable. In addition, the scale efficiency is of the order of 0,652. Which implies that family  poultry farms can reduce input use by proportions of 0,545 ; 0,502 and 0,348.Most farmers, 59,09% operate in the zone of decreasing returns to scale, 27,27% under increasing returns to scale and 13,64% under constant returns to scale.The main covariates of technical efficiency below CRS and VRS are : age of producer ; the level of study ; proximity between farms ; exposure to frequent risk ; the average weight at the laying entrance reduces technical efficiency. While owning a means of transportation ; saving in a financial institution ; the contract between input supplier and famer ; access to credit ; access to extension service ; the housing structure ; the frequency of daily consumption and the breed to be  raised positively explain the technical efficiency of poultry farms.